2002
DOI: 10.1007/s00444-002-0356-0
|View full text |Cite
|
Sign up to set email alerts
|

Reformüberlegungen unter besonderer Berücksichtigung familienrechtlicher und personenstandsrechtlicher Fragen

Abstract: The law as it stands is too rigid and restrictive with regard to the availability of reproductive techniques.On the other hand, the legal rules do not protect the interests of the persons concerned in a satisfactory manner. Professional rules that further limit availability are not justifiable.A reform of the legal rules should allow donation.Donation of sperm, oocytes, and embryos should be documented by a central registry.Information and consultation should substitute prohibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this point it appears that the Embryo Protection Law is much more liberal than many of the interpretations derived from it. This interpretation has already been debated in previous studies and was confirmed both scientifically and legally in subsequent years (2000) [9][10][11]. Even if one allows for the attempts by fertility doctors to avoid higher-order multiple pregnancies, the described procedure with the transfer of 2 embryos means that it is possible to offer couples a successful method which is compatible with the Embryo Protection Law [3][4][5]12].…”
mentioning
confidence: 90%
“…In this point it appears that the Embryo Protection Law is much more liberal than many of the interpretations derived from it. This interpretation has already been debated in previous studies and was confirmed both scientifically and legally in subsequent years (2000) [9][10][11]. Even if one allows for the attempts by fertility doctors to avoid higher-order multiple pregnancies, the described procedure with the transfer of 2 embryos means that it is possible to offer couples a successful method which is compatible with the Embryo Protection Law [3][4][5]12].…”
mentioning
confidence: 90%
“…Theoretically, the right of a father–child relationship has to be considered, e.g. the right to visit the genetic father or questions of heritage (Coester‐Waltjen 2002).…”
mentioning
confidence: 99%